Pengaruh Kompetensi Sumber Daya Manusia, Penerapan Sistem Akuntansi Keuangan Daerah, Dan Sistem Pengendalian Intern (Internal Audit) Terhadap Kualitas Laporan Keuangan Pemerintah Daerah (Studi Empiris pada SKPD Kabupaten Kuantan Singingi) - Yensi, Desy Sefri; Hasan, Amir; Anisma, Yuneita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of human resource competencies, implementation areas of financial accounting system and internal control system (internal audit) on the quality of financial reporting by local governments throughout the research object SKPD KuantanSingingi district numbering 26 on education. The sampling technique using simple random sampling. The method of data collection is by distributing questionnaires. Analysis using multiple regression. The results of this study it is concluded that the competency of human resources and the application of financial accounting systems area positively significant effect on the quality of financial reports while the variable region of the internal control (internal audit) does not affect the quality of local government financial reports. In this study the magnitude of the effect that the R2 of 0.448 or 44.8% indicated that the competency of human resources and the application of financial accounting system areas affecting the quality of financial reporting area of 44.8%, because in the world of government, every part of government must by right people, which has competence in accordance with the predetermined qualifications. So is the application of financial accounting system has an influence on the quality of the region's financial statements due to the implementation of local area financial accounting system is a medium that can support to produce reliable financial reports and are able to prepare and present the financial statements of qualified regional and meet government quality characteristics of financial statements predefined area. While by 55.2% influenced by other variables.Keywords: quality of financial reports, human resources competencies,implementation areas of financial accounting system and internal controlsystem (internal audit)